Empowerment of Religious Facilities to Enhance Religious Education in Muara Uwai Village, Bangkinang, Kampar, Riau; Through Thematic Community Service Activities - Abdul Aziz Shidiq; Daryanto Setiawan; Ahmad Zaky (ASSUNNAH PRESS, 2025)
The obligation of a student after acquiring knowledge and practice is to impart it to others. Kuliah Kerja Nyata Tematik (KKNT) is one of the activities aimed at disseminating knowledge within the community. One of the places where KKNT is practiced is the village of Muara Uwai, Bangkinang Subdistrict, Kampar District, Riau. This village faces several issues, including the community's limited religious education, their inability to read the Quran properly, and children's lack of proficiency in religious practices. These issues are addressed by utilizing available assets, such as mosques and Quranic houses for teaching. The research employed the Action Research method with the ABCD (Asset Based Community Development) model. The results indicate that KKNT activities have improved religious education, Quranic reading skills, and knowledge of proper religious practices among the children and youth of Muara Uwai. However, the research also identified challenges in enhancing religious education among mothers and their Quranic reading abilities due to time constraints, which make it difficult for them to participate in activities organized by KKNT students, given their predominantly farming professions